X + 8Y = 19 ...(1)

3X - Y = 4 ...(2)

multiply the second equation by 8

8 x (2) => 24X - 8Y = 32 ....(3)

add the first and third equations

(1)+(3)=> X + 8Y +24X -8Y = 19 + 32

=> 25X =51

=> **X = 51/25 **

Substitute this value in the second equation

=> 3X - Y = 4

=>3 (51/25) - Y = 4

=> Y = 3(51/25) -4

=> Y = (153/25) - 4

=> Y = (153/25) - (100/25)

=>**Y = 53/25**

The set of linear equations

x + 8y = 19 ...(1)

3x - y = 4 ...(2)

has to be solved for x and y

From (1)

x = 19 - 8y

Substitute in (2)

=> 3(19 - 8y) - y = 4

=> 57 - 24y - y = 4

=> 53 = 25y

=> y = 53/25

x = 51/25

**The solution of the set of equations is x = 51/25, y = 53/25**